CHARACTERISATION, EVALUATION AND DENSITY FUNCTIONAL ANALYSIS OF CILNIDIPINE-NICOTINAMIDE COCRYSTALS DEVELOPED BY LIQUID ASSISTED GRINDING TECHNIQUE: A SUSTAINABLE APPROACH FOR ENHANCED SOLUBILITY - CHERUKKOTH, RENJISH; ITTIYAVIRAH, SIBI P.; HARINDRAN, JYOTI; NAIR C. R., SUDHAKARAN (International Journal of Applied Pharmaceutics, 2024)
Objective: Improving the solubility of poorly water-soluble drugs has always been a challenge in drug development. This study aimed to enhance the aqueous solubility of a poorly water-soluble drug, Cilnidipine, by cocrystallisation method using liquid-assisted grinding (LAG) technique with Nicotinamide as the coformer. The study also aimed to understand the mechanism of cocrystal formation by quantum mechanical calculations. Methods: The Cilnidipine-Nicotinamide cocrystals were prepared in various stoichiometric ratios using the liquid-assisted grinding (LAG) technique. The cocrystals obtained were characterised by vibrational spectroscopy, thermal methods such as differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD) and surface morphology by field emission scanning electron microscopy (FE-SEM). The cocrystals were evaluated for saturation solubility, and the mechanistic study of cocrystal formation was performed using the Gaussian 09 software package. Results: FT-IR spectra of the formulated cocrystal indicated the intermolecular hydrogen bond formation between-N-H of Nicotinamide and the nitro group of Cilnidipine. DSC analysis showed a single endotherm at 96.76 °C, PXRD patterns were different from that of the reactants, and FE-SEM analysis revealed the changes in the surface morphology of the obtained cocrystal. The prepared cocrystal showed a 26.36-fold enhancement in the aqueous solubility of Cilnidipine. The DFT study demonstrated the formation of a strong intermolecular hydrogen bonding between the nitro-oxygen atom of Cilnidipine and the amide hydrogen atom of Nicotinamide in cocrystal formed. Conclusion: This study highlights the potential of the liquid-assisted grinding method for preparing cocrystals as a sustainable and reliable approach to address the challenges posed by poorly water-soluble drugs.